A new fossil drywood termite species from the Late Eocene of France allied to Cryptotermes and Procryptotermes (Isoptera: Kalotermitidae) - Engel, Michael S.; Nel, André (Novitates Paleoentomologicae, 2015)
A new fossil genus and species of drywood termite (Kalotermitidae) is described and figured from the Late Eocene of southern France.  Huguenotermes septimaniensis Engel & Nel, new genus and species, is closely allied to Cryptotermes Banks and Procryptotermes Holmgren, perhaps representing part of the stem group leading to the Cryptotermes-Procryptotermes clade.